Framing world monetary system reform: Fritz Machlup and the Bellagio Group conferences - Connell, Carol M. (PSL Quarterly Review, 2011)
This paper explores the influence of Fritz Machlup and the Bellagio Group on world monetary reform. After an examination of the literature, the paper addresses research into Machlup’s framing of the problem of world monetary reform, his method, his selection of economists to join the Bellagio Group, his close working relationship with the treasury and central bank officials who were the deputies of the Group of Ten, and his creation of a broad platform of joint conferences, papers and books to promote their work. Taking an historico-biographical approach, this paper draws on the archives and published works of Fritz Machlup, Robert Triffin and their contemporaries. JEL Codes: B22, B31, F31, F33